Оцінка граничних частот смуг пропускання поширенних кабельних ліній передачі - Бойченко, С. В. (ХНУРЕ, 2025)
The calculation and evaluation of the bandwidth cutoff frequencies of common cable transmission lines with different dielectric filling from the point of view of their use for transmitting broadband signals have been carried out.
Keywords: смуг пропускання ліній передачі; кабельна лінія передачі